The effect of Material to Solvent Ratio to The Flavonoid Content and Free Radical Scavenging Activity of Extract of Morinda Citrifolia L Leaves - Ramayani, Septiana Laksmi; Fitria Rohmawati; Yasmine Savira Rahmadani (Tropical Biopharmaca Research Center, IPB University, 2022)
The flavonoid compound in Noni leaves (Morinda citrifolia) are efficacious as free radical scavengers. This research aimed to know the influence of the ratio of materials and a solvent (M:S=1:10; M:S=1:15; M:S=1:20) on the flavonoid content and free radical scavenging activity of extract of noni leaves. Extraction was carried out using the Microwave Assisted Extraction method and the free radical scavenging activity were determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH). The results showed that the material-solvent ratio had a significant effect on the yield, total flavonoid content, and free radical scavenging activity. The material to solvent ratio 1: 20 resulted in the highest yield, total flavonoid content, and free radical scavenging activity compared to other solvent-solvent ratios.